Răspuns :
Explicație pas cu pas:
a=3×3+2×4×[7+6×(2×10-3)-2×1]-1000:10=
a=9+8×[7+6×(20-3)-2]-100=
a=9+8×(7+6×17-2)-100
a=9+8×(7+102-2)-100
a=9+8×(109-2)-100
a=9+8×107-100
a=9+856-100
a=865-100
a=765
b=[9+17+3×(12-7)]:2-5×2
b=(9+17+3×5):2-10
b=42:2-10
b=21-10
b=11
(765+11):25
776:25
nu îmi dă nici un rezultat cred că ai scri greșit
Răspuns:
[tex]\bf \red{\big(a+b\big):25=31}[/tex]
Explicație pas cu pas:
[tex]\bf a = \underline{3 \cdot 3} + 2 \cdot 4 \cdot \big[7+6\cdot (\underline{2 \cdot 10} - 3) - 2 \cdot 1\big] - 1000:10[/tex]
[tex]\bf a = 9 + 2 \cdot 4 \cdot \big[7+6\cdot (\underline{20 - 3}) - \underline{2 \cdot 1}\big] - 1000:10[/tex]
[tex]\bf a = 9 + 2 \cdot 4 \cdot \big(7+\underline{6\cdot 17}- 2\big) - \underline{1000:10}[/tex]
[tex]\bf a = 9 + 2 \cdot 4 \cdot \big(7+102- 2\big) - 100[/tex]
[tex]\bf a = 9 + 2 \cdot 4 \cdot \big(7+100\big) - 100[/tex]
[tex]\bf a = 9 + 2 \cdot 4 \cdot 107 - 100[/tex]
[tex]\bf a = 9 + 8 \cdot 107 - 100[/tex]
[tex]\bf a = 9 + 856 - 100[/tex]
[tex]\bf a = 865 - 100[/tex]
[tex]\bf \purple{\underline{a = 765}}[/tex]
[tex]\bf b = 9+ \big[7+3\cdot (\underline{12 - 7})\big]: 2-5\cdot 2[/tex]
[tex]\bf b = 9+ \big(7+\underline{3\cdot 5}\big): 2-\underline{5\cdot 2}[/tex]
[tex]\bf b = 9+ \big(\underline{7+15}\big): 2-10[/tex]
[tex]\bf b = 9+ \underline{22: 2}-10[/tex]
[tex]\bf b = 9+ 11-10[/tex]
[tex]\bf b = 20-10[/tex]
[tex]\bf \blue{\underline{b = 10}}[/tex]
[tex]\bf \big(a+b\big):25=[/tex]
[tex]\bf \big(765+10\big):25=775:25=31\implies \red{\underline{\big(a+b\big):25=31}}[/tex]
Varianta corectă → b)
==pav38==
Baftă multă !